Oral malignant acanthosis nigricans associated with endometrial adenocarcinoma - Chu, Han-Wen (Int J Oral Sci, 2014)
We report a 59-year-old patient with malignant acanthosis nigricans associated with metastasis of endometrial carcinoma. The patient presented papillomatosis lesions that appeared to be benign on multiple skins of body folds, particularly on lips. The lesions in lips and axilla had histological characteristic appearances of acanthosis nigricans, while the masses in abdomen and pelvis were metastasis endometrial adenocarcinoma. The article highlights the importance of biopsy and histopathological diagnosis in presumed benign lesions and the role of doctors in screening for body internal tumors.